Front-End vision and multi-scale image analysis multi-scale computer vision theory and applications, written in Mathematica - Romeny Bart M ter Haar (Dordrecht Kluwer Academic, 2003)
Multi-scale approach is interwoven in every chapter of the book.It builds on the cross fertilization between human visual perception and multi-scale computer vision (`scale-space') theory and applications. Overall the book presents a new and effective app
Accompanies a CD-ROM bearing acc no D635
Keywords: Computational imaging; Image processing-digital techniques